PEMANFAATAN LIMBAH SERPIHAN TANDUK KERBAU MENJADI PRODUK PEGANGAN GOLOK DENGAN TEKNOLOGI TEPAT GUNA - Rohimat, R Ismed (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2019)
Recently, the usage of animal horn in Indonesia as a hand craft has a great attention especially for a dirk handycrafter. The shortage of such horn as raw material becomes a problem for the horn and dirk handycrafter. Implication of that is a gap between demand and supply in the market. To over come this condition, we design two machines-milling machine and pressing machine- that changing the scrap of horn processing into a useable raw material. The idea is converted the waste by using milling and pressing process.The result not only profitable for the horn handy-crafter, it also gives benefition solution for the green production process by making a better environment